Using Bibliometric Analysis to Explore Research Trend of Euro-6 from 2010 to 2019 - Yadav, Dr. Satendra Kumar (International Journal of Advanced Science and Technology, 2020)
The study aims to identify the research trend of euro- 6 by analyzing 1401 articles published in documents indexed in Scopus database in a ten years period between 2010 and 2019. The study maps the intellectual structure of the Euro-6 research area. The results provide fundamental insights and recent trends in the development of Euro -6 research area.